E- FAWATEERcom Adoption in Jordan : A Proposed Frame Work User Perspective - Alibraheem, Mohammad Haider M. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper discusses whether E- FAWATEERcom Adoption in the Jordan. By utilizing the unified theory of acceptance and use of technology (UTAUT), the paper proposes a framework on the antecedents of E- FAWATEERcom. The proposed framework could give significant practical insight and implication to E- government authorities worldwide that implement E- FAWATEERcom, especially the Jordanian authorities.